Changes in apolipoproteins following ingestion of a beverage delivering β-hydroxybutyrate: results from a randomized placebo-controlled trial - Liu, Yutong; Kimita, Wandia; Bharmal, Sakina H.; Petrov, Maxim S. (Frontiers in Nutrition, 2026)
BackgroundApolipoproteins play important roles in the metabolism of triglyceride-rich lipoproteins. Ketone monoester β-hydroxybutyrate (KEβHB) has been shown to reduce the circulating levels of remnant cholesterol and triglycerides. However, the mechanisms behind this action remain unknown.AimTo investigate the effect of KEβHB supplementation on apolipoproteins and to study whether circulating levels of triglycerides play a role in this effect.MethodsThe study was a randomized placebo-controlled trial, registered at https://www.clinicaltrials.gov/ (NCT03889210). It included 18 adults (12 men and 6 women) with prediabetes (defined as per the American Diabetes Association criteria). Following an overnight fast, participants ingested a KEβHB or a placebo beverage in a cross-over manner. Serial blood samples were collected from baseline to 150 min at intervals of 30 min. The endpoints were changes in apolipoprotein (apo) A-I, apo B, apo B-48, apo C-II, apo C-III, and apo E. Area under the curve (AUC) analyses were calculated to estimate changes in the studied apolipoproteins over time. Participants were further stratified into ‘hypertriglyceridemia’ and normal triglyceride levels subgroups.ResultsIngestion of the KEβHB beverage led to a significantly higher AUC for apo C-II (p = 0.023) in the overall cohort. No statistically significant differences in AUCs were found for the other studied apolipoproteins. The subgroup analysis showed significantly lower levels of apo B (and higher levels of apo C-II) after the KEβHB beverage in individuals with hypertriglyceridemia only. No significant associations were found for the other studied apolipoproteins in either subgroup.ConclusionExogenously induced acute ketosis resulted in a significantly elevated apo C-II compared with the placebo. Further, the levels of apo B were significantly lowered following ingestion of the KEβHB beverage only among individuals with hypertriglyceridemia. Acute nutritional ketosis may be considered as a potential approach to reduce atherogenic triglyceride-rich lipoproteins in individuals at high cardiovascular disease risk.